2004
DOI: 10.1529/biophysj.103.032714
|View full text |Cite
|
Sign up to set email alerts
|

Structure of (KIAGKIA)3 Aggregates in Phospholipid Bilayers by Solid-State NMR

Abstract: The interchain (13)C-(19)F dipolar coupling measured in a rotational-echo double-resonance (REDOR) experiment performed on mixtures of differently labeled KIAGKIA-KIAGKIA-KIAGKIA (K3) peptides (one specifically (13)C labeled, and the other specifically (19)F labeled) in multilamellar vesicles of dipalmitoylphosphatidylcholine and dipalmitoylphosphatidylglycerol (1:1) shows that K3 forms close-packed clusters, primarily dimers, in bilayers at a lipid/peptide molar ratio (L/P) of 20. Dipolar coupling to addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 53 publications
6
68
0
Order By: Relevance
“…Recently, a solid-state NMR investigation of K3, 108 a synthetic analogue of PGLa, has provided a direct structural evidence of peptide dimerization in PC/PG bilayers. 141 The combination of distance and orientation information obtained from rotationalecho double resonance (REDOR) 142 experiments on mixtures of differently labeled K3 peptides have indicated a parallel dimer structure in which K3 helices intersect at a cross-angle of approximately 208.…”
Section: The Mode Of Action Of Linear Ampsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a solid-state NMR investigation of K3, 108 a synthetic analogue of PGLa, has provided a direct structural evidence of peptide dimerization in PC/PG bilayers. 141 The combination of distance and orientation information obtained from rotationalecho double resonance (REDOR) 142 experiments on mixtures of differently labeled K3 peptides have indicated a parallel dimer structure in which K3 helices intersect at a cross-angle of approximately 208.…”
Section: The Mode Of Action Of Linear Ampsmentioning
confidence: 99%
“…145 While the barrel-stave mechanism seems to hold for noncell-selective lytic peptides only, the carpet mechanism appears to be a more general permeabilization mechanism that is responsible for the lytic action of peptides in negatively charged lipid bilayers such as the outer leaflet of the bacterial cell membrane. 11 The list includes cecropins, 146 141 melittin, 156 and the -sheet protegrin. 176 We should also note that in the case of melittin, there have been other earlier and more recent reports that indicate the peptide may form barrel-stave-type pores in zwitterionic membranes 101,102,177,178 and act via a detergent-like permeabilization mechanism in anionic lipids.…”
Section: The Mode Of Action Of Linear Ampsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong 13 C-31 P dipolar coupling showed that the peptide must lie flat on the membrane surface, in order for all carbons to be close to a phospholipid head group. More recently, a combination of different 13 C/ 15 N/ 19 F/ 31 P REDOR experiments on the antimicrobial peptide K3 have demonstrated that it can self-assemble into head-to-head dimers at high concentrations in the membrane (99,100). Finally, a different type of experiment using slow sample spinning, 2D SSRS-MASE, has revealed the relative orientation of two CO CSA tensors on consecutive amino acids in melittin (88).…”
Section: Nmr On Peptidesmentioning
confidence: 99%
“…When this approach was applied to PGLa, it revealed different tilt angles of the peptide in the membrane, depending on the peptide concentration and lipid composition (74,116). The re-alignment was interpreted in terms of dimerization, in analogy to the results on the related K3 peptide that has been extensively characterized from REDOR distances, including 19 F-13 C constraints (99,100). In a different approach, 19 F NMR can be used to probe the depth of membrane immersion by O 2 quenching.…”
Section: F Nmr On Peptidesmentioning
confidence: 99%